Comprehensive approach for the genetic diagnosis of patients with Waardenburg syndrome - Buonfiglio, Paula Inés (2023)
Waardenburg syndrome (WS) is one of the most common syndromic forms of genetic hearing loss (HL), accounting nearly for 2-5% of congenital HL. It is characterized by the presence of hearing impairment in association with pigmentation abnormalities that may affect the skin, hair, and/or eyes. WS is divided into four subtypes according to different concomitant phenotypes and its generally of autosomal dominant inheritance. Up to date, seven genes are related to WS: PAX3, MITF, EDNRB, ENDR, SOX10, KITLG and SNAI2. Disease-causing variants are mainly single nucleotide variants (SNVs), though copy number variants (CNVs) have also been reported. The aim of this work is to identify the genetic causes of WS in four family cases with a dominant mode of inheritance.As the first step Whole Exome Sequencing (WES) was performed for SNVs screening, filtering out the target genes. When negative, CNVs were analyzed using DECoN tool on WES raw data. Multiplex ligation-dependent probe amplification (MLPA) was carried out to confirm and segregate CNVs identified in the family members.Three of the 4 families analyzed carried heterozygous pathogenic variants: one SNV and two CNVs in the WS target genes. In family #1 a stop variant (NM_001354604.2:c.1198C>T p.Arg400*) was detected in MITF and segregated in one affected son of the family. In family #2 a deletion of 1 exon in PAX3 gene was detected and segregated also in the affected mother. In family #3, remarkably, a large novel deletion comprising 7 genes including SOX10 was detected in the exome CNVs analysis. The complete loss of SOX10 was confirmed and also segregated in the affected family members by MLPA.The combination of techniques and bioinformatic analysis resulted in a better diagnostic rate and in a substantial improvement in the molecular diagnosis of patients. These results highlight the importance of combining different strategies to achieve diagnosis leading to an accurate genetic counseling.